Pyrolysis kinetics of short rotation coppice poplar biomass. (15th September 2020) - Rego, Filipe; Soares Dias, Ana P.; Casquilho, Miguel; Rosa, Fátima C.; Rodrigues, Abel
Abstract: Woody biomass can be converted into green fuels by advanced conversion technologies such as gasification and pyrolysis. Due to the complexity of woody biomass, the thermochemical decomposition mechanisms are complex and the knowledge of pyrolysis kinetics is mandatory for optimization of the process and reactor design of commercial scale biorefineries. Pyrolysis kinetics of short rotation coppice (SRC) poplar biomass (nine different clones) was studied using non-isothermal thermogravimetry. By using differential thermogravimetry data, obtained for heating rates of 10–50 K/min, the Kissinger model-free methodology showed activation energies in the range 108–320 kJ/mol, similar to those reported in the literature for cellulose pyrolysis. Isoconversional approaches of Flynn-Wall-Ozawa (FWO) and Kissinger-Akahira-Sunose (KAS) obtained similar values of activation energy (81–301 kJ/mol and 90–306 kJ/mol, respectively. The kinetics parameters obtained by the FWO and KAS methods were higher than data reported in the literature for other biomasses, and a correlation between activation energy and the lignin content of the biomass samples was found. The pyrolysis activation energy seems to have no significant effect on the pyrolysis product yields, probably because, under the tested conditions (fixed bed reactor, 773 K), pyrolysis was controlled by mass and/or heat transfer limitations instead of kinetics control. Graphical abstract: Image 1 Highlights: SRC poplar biomass pyrolysis kinetics were evaluated by TGA and model-free methods. Different poplar genotypes presented analogous kinetics behaviours. Activation energies from Kissinger method were similar to that of cellulose. Higher activation energy values were correlated to higher biomass lignin content. Activation energies had no significant effect on pyrolysis in a fixed bed reactor.